PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS II SD NEGERI 2 BEBALANG - I Dewa Ayu Sukaasih Maharti; I Nengah Sueca; I Nyoman Sudirman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low early reading skills of second-grade students at SD Negeri 2 Bebalang, particularly in pronunciation, intonation, fluency, voice clarity, and reading completeness. Many students still struggled to recognize letters, blend syllables, and read more complex words. Teacher-centered instruction and limited use of engaging media further contributed to this condition. This study aims to describe the implementation of the Project Based Learning (PjBL) model assisted by visual media and determine its effect on improving early reading skills. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were 11 second-grade students at SD Negeri 2 Bebalang. Data were collected through observation and early reading tests, then analyzed descriptively by comparing results from the pre-cycle, Cycle I, and Cycle II. The results showed significant improvement. The average reading score increased from 62.64 in the pre-cycle to 72.09 in Cycle I and 78.73 in Cycle II. The percentage of students achieving mastery rose from 54.55% to 72.73% and reached 81.82% by the end of the study. Improvement occurred across all assessed aspects: pronunciation, intonation, fluency, voice clarity, and reading completeness. Thus, the PjBL model supported by visual media proved effective in enhancing early reading skills of second-grade students at SD Negeri 2 Bebalang.